2021
DOI: 10.1371/journal.pone.0253864
|View full text |Cite
|
Sign up to set email alerts
|

The KrasG12D;Trp53fl/fl murine model of undifferentiated pleomorphic sarcoma is macrophage dense, lymphocyte poor, and resistant to immune checkpoint blockade

Abstract: Sarcomas are rare, difficult to treat, mesenchymal lineage tumours that affect children and adults. Immunologically-based therapies have improved outcomes for numerous adult cancers, however, these therapeutic strategies have been minimally effective in sarcoma so far. Clinically relevant, immunologically-competent, and transplantable pre-clinical sarcoma models are essential to advance sarcoma immunology research. Herein we show that Cre-mediated activation of KrasG12D, and deletion of Trp53, in the hindlimb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 56 publications
(98 reference statements)
1
9
0
Order By: Relevance
“…This murine model of UPS is resistant to anti-CTLA4 and anti-PD-1 monotherapy (Figures 8A, B) and documented by others (29). We have observed late UPS tumor relapses in mice treated with DMXAA after near complete tumor eradication (relapses, Figures 1C, D).…”
Section: Sting Therapy Is Synergistic With Immune Checkpoint Blockade...supporting
confidence: 81%
See 1 more Smart Citation
“…This murine model of UPS is resistant to anti-CTLA4 and anti-PD-1 monotherapy (Figures 8A, B) and documented by others (29). We have observed late UPS tumor relapses in mice treated with DMXAA after near complete tumor eradication (relapses, Figures 1C, D).…”
Section: Sting Therapy Is Synergistic With Immune Checkpoint Blockade...supporting
confidence: 81%
“…The development of the syngeneic KP UPS cell line used in these experiments is described and characterized by Hildebrand et al (2021) (29), and also previously by DuPage et al (2012) (31) and Kirsch et al (2007) (30). Briefly, spontaneous UPS tumors were generated in conditional Trp53 fl/fl and Kras G12D/+ mice via lenti-Cre (University of Iowa Viral Vector Core; FIVCMVCre VSVG) mediated Trp53 deficiency and activation of the Kras G12D oncogene subperiosteally in the hindlimb of female C57Bl/6 mice which results in establishment of primary UPS tumors exclusively in the proximal tibia of the hindlimb.…”
Section: Tumor Modelmentioning
confidence: 99%
“…As expected, transplanted tumors showed a more inflamed microenvironment with increased activity of suppressive M2 macrophages and activated CD8+ T cells. Treatment with PD-1 blockade further increased CD8+ T cell activity with a decrease in M2 macrophages, which was not recapitulated in the primary tumors [17] . However, another study performed similar experiments in the KP model, with conditional Kras G12D mutation plus Tp53 deletion, comparing the immune infiltrates and response to checkpoint blockade in primary tumors to those transplanted into naïve C57Bl/6 mice.…”
Section: Preclinical Investigations In Murine Modelsmentioning
confidence: 88%
“…Additionally, those models that do exist fail to capture the heterogeneity within a large number of sarcoma subtypes, genetic and immune heterogeneity within sarcomas even of the same subtype, and inter-and intratumoral heterogeneity within the same patient. Wisdom et al [17] recently reported immune profiling in a high mutational load murine model of undifferentiated pleomorphic sarcoma (UPS), generated by inducing conditional Trp53 fl/fl deletions with subsequent injection of the carcinogen 3-methylcholanthrene in the same site. The authors demonstrated resistance to radiation and PD-1 blockade in primary tumors that evolved under immune pressure, compared to transplanted tumors in different mice, which were more readily rejected.…”
Section: Preclinical Investigations In Murine Modelsmentioning
confidence: 99%
See 1 more Smart Citation